2009
DOI: 10.1042/bj20091035
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and inhibitors of LRRK2, a protein kinase mutated in Parkinson's disease

Abstract: The LRRK2 (leucine-rich repeat protein kinase-2) is mutated in a significant number of Parkinson’s disease patients, but little is known about its regulation and function. A common mutation changing Gly2019 to serine enhances catalytic activity, suggesting that small-molecule inhibitors might have utility in treating Parkinson’s disease. We employed various approaches to explore the substrate-specificity requirements of LRRK2 and elaborated a peptide substrate termed Nictide, that had 20-fold lower Km and near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
246
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(284 citation statements)
references
References 39 publications
36
246
2
Order By: Relevance
“…It is speculated that the ATP-binding site is the direct target for many of the inhibitors, but the exact binding mechanism is unknown. We were able to cocrystallize the Roco4 kinase domain with H1152, which originally was identified as a rho-associated protein kinase (ROCK) inhibitor but recently was reported to have nearly the same inhibitory effect on LRRK2 (35). H1152 also was found to inhibit Roco4 kinase activity, and binding is ATP competitive (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is speculated that the ATP-binding site is the direct target for many of the inhibitors, but the exact binding mechanism is unknown. We were able to cocrystallize the Roco4 kinase domain with H1152, which originally was identified as a rho-associated protein kinase (ROCK) inhibitor but recently was reported to have nearly the same inhibitory effect on LRRK2 (35). H1152 also was found to inhibit Roco4 kinase activity, and binding is ATP competitive (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…To date, several relatively nonspecific kinase inhibitors, such as H1152, staurosporine, sunitinib, and GW5074, and more specific LRRK2 inhibitors, such as LRRK2-IN-1, have been identified (34,35). It is speculated that the ATP-binding site is the direct target for many of the inhibitors, but the exact binding mechanism is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of autophosphorylated LRRK2 by matrix assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometery revealed that Ser1403, Thr1404, Thr1410, Thr1491 in the ROC domain, as well as Thr1967 and Thr1969 in the kinase domain, can all be autophosphorylated (60). Kinase assays of LRRK2 using various synthetic peptides showed that the enzyme prefers to phosphorylate Thr over Ser residues, and one study developed a synthetic peptide, Nictide, as a LRRK2 substrate for in vitro kinase assays (61).…”
Section: Molecular Biological Features Of Lrrk2 and Its Pathological mentioning
confidence: 99%
“…Because LRRK2 mutations are inherited in an dominant manner and the most prevalent mutation, G2019S, increases kinase activity, it will be easier to develop a LRRK2 kinase inhibitor instead of developing a drug to enhance function of the FPD recessive genes. Two recent papers tested LRRK2 kinase activity with several known kinase inhibitors (61,103). Nichols et al tested the effectiveness of three Rho kinase (ROCK) inhibitors and showed that Y-27632 and H-1152, but not GSK429286A, suppressed LRRK2 with similar potency as their activity against ROCK (61).…”
Section: Lrrk2 As a Pd Therapeutic Target Genementioning
confidence: 99%
“…Although a clear picture has yet to emerge of a consistent alteration in these due to mutations, data from a number of groups has highlighted the importance of the kinase activity of LRRK2 in cell death linked to mutations 7,8 . Recent publications have reported inhibitors targeting the kinase activity of LRRK2, providing a key experimental tool [9][10][11] . In light of these data, it is likely that the enzymatic properties of LRRK2 afford us an important window into the biology of this protein, although whether they are potential drug targets for Parkinson's is open to debate.…”
mentioning
confidence: 99%